Segmentary Damage Constitutive Model and Evolution Law of Rock under Water-Force Coupling Action of Pumped Storage in Deep Mine - Ji’an Luo; Liangliang Wang (Energies, 2023)
The deformation and failure of surrounding rock mass under different water environments is a basic mechanical problem encountered in the safe operation of ground pumped storage power station and abandoned mine pumped storage power station. According to the influence of different water environments on the failure characteristics of deep surrounding rock mass, it is necessary to summarize the damage evolution law of deep rock mass under different water environments and construct the constitutive model. In this paper, the loading mechanical test is carried out after the natural immersion of the rock in different water environments. The influence of the change of the geological water environment on the damage evolution characteristics of the rock is analyzed from the perspective of the deterioration of the mechanical parameters. On this basis, the damage statistical constitutive model is constructed, and the damage evolution analysis is carried out. The results show that the degradation degree of mechanical parameters such as compressive strength and elastic modulus of sandstone is in the order of distilled water immersion, simulated groundwater immersion and natural state. The damage evolution of sandstone under water–rock interaction is divided into four stages: no damage, rapid damage, deceleration damage and failure. The theoretical curve of the model is in good agreement with the uniaxial test curve of rock under different water environments. The segmented damage constitutive model based on the long compaction stage of sandstone under water–rock interaction reasonably reflects the change of stress–strain relationship of damage failure, and the physical meaning of parameters is clear.